Proses Negosiasi Antara UMKM A.M Tahu Dan Pemasok Bahan Baku Produksi (Forum Agribisnis, 2024)
SME’s are an industry that play an important role in the Indonesia’s economic development. A.M Tahu as one of SME’s have problems in fulfilling raw materials. The existence of special orders and moral hazard from suppliers were often obstacles in the production process so that A.M. Tahu is needed to make a negotiation process to get affordable prices, good quality, and flexibility in the quantity of raw materials with a limited choice of suppliers. The negotiation process certainly does not immediately reach the desired agreement, but efforts need to be made to convince both parties. The research aims to determine the negotiation process that occurs between A.M Tahu and raw material suppliers in reaching agreements. The types of data used in this study are primary and secondary data using AHP (Analysis Hierarchy Process) analysis methods and qualitative descriptive. The results showed that the negotiation process for A.M Tahu has several stages in reaching an agreement between the two parties, including starting from preparation, meetings, offers, and finally agreements. A.M Tahu gets a more convenient raw material price of Rp3,000 per kilo than the price should be, soybean quantity flexibility, and good quality assurance of soybean grain raw materials. A.M Tahu is also prioritized to choose suppliers who are outside the sub-district, and make raw material variables the main thing to consider in supplier selection.